A comparative analysis on single and two phase casson fluid under aligned magnetic field effect and newtonian heating - Hassan, Tijjani Lawal; Abdul Rahman, Mohd Kasim; Mohd Haziezan, Hassan (Akademi Baru, 2023)
This research investigates the impact of aligned magnetic fields and Newtonian heating on single and two-phase Casson fluid (a mixture of Casson fluid and dust particles), addressing a notable knowledge gap in comparing the two fluid models under the same effect. The problem of this study lies in the need to understand the similarities or differences in the reaction of these fluids to external forces. To achieve this, the governing equations for both fluids were formulated using a boundary layer approximation and numerical solutions were obtained utilizing the 'bvp4c' function within MATLAB software. The analysis revealed comparable trends in flow and thermal behaviour between the two fluids, it also showed that the magnetic field exerted a more pronounced influence on flow properties compared to forces such as buoyancy and inertia. Conversely, Newtonian heating conditions had a more significant impact on thermal properties compared to the magnetic field. Additionally, the single-phase Casson fluid showed higher velocity and temperature profiles than the two-phase Casson fluid phases. These findings suggest that the presence of dust particles reduces the velocity and temperature magnitudes of the Casson fluid.